Problems Faced by Diploma Engineering Students in Learning Chemical Reaction - Reshmi, Dhan Bahadur (Kaladarpan कलादर्पण, 2022)
The purpose of this paper is to identify problems faced by the students in chemical reaction learning who had completed their school education from public and institutional schools. In addition, to the analysis of relationship between both group of students in terms of Chemistry- I result, learning chemical reaction, partial method and oxidation number method. For this survey study design, total 400 participants had been sampled, and purposively determined with 200 from each schooling group. Three hypothesises were formulated and tested to analyze relation between public and institutional schooling group participants in context of prescribed variables. The findings indicated that there were no significant difference between the groups and had weak correlation between tested variables. The study enlighted that chemistry teaching strategy can be improved and it can be truly begin to find the solutions of problems faced by students in classroom teaching. The author hopes that this paper will contribute for minimize discriminated the attitudes of society towards Public and institutional schools for their children’s education. Similarly, it will motivate the teachers for applying the student- friendly teaching manner, and will guide the concerned bodies reform chemistry course.